REPRESENTAÇÕES SOCIAIS SOBRE OS SABERES DOCENTES NECESSÁRIOS A SUA PRÁTICA DOS PROFESSORES DE UMA INSTITUIÇÃO DE ENSINO SUPERIOR PRIVADA DE PONTA GROSSA – PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This paper presents an analysis of the social representations of teachers in Higher Private Education Institutions in Ponta Grossa - PR, on teacher knowledge related to teaching put into practice. The research objectives were: pointing, social representations of teachers' work; clarify the extent to which teacher knowledge related pedagogical practice in the classroom. Used as theoretical background contributions of the Theory of Social Representations of Moscovici (1978), Jodelet (1984, 1993, 2001, 2007), Sá (1996, 1998) and Abric (2001) with regard to the concepts and approaches of social representations, as well as on the core of social representations.Yet, used as theoretical background conceptions of knowledge and teaching knowledge concerning the teaching explained by the authors (SHULMAN, 1986; TARFIF; LESSARD, 2005; GAUTHIER, 1998) the research approach chosen by the analysis quantitative and qualitative through the following instruments: questionnaire with semi - structured questions with pre - defined for a hundred teachers IES Ponta Grossa in various disciplines, and individual interviews with thirty teachers selected the posterity, for analysis and record the interviews. The categories were created from the theoretical framework of social representations and teaching knowledge and the process of data analysis followed the steps of content analysis defined by Bardin (1978). These steps were performed using the software EVOC (VÈRGES, 2002) ATLAS TI and ALCESTE.The results indicate that among the types of knowledge mentioned in the work, content knowledge was the most cited by teachers, then pedagogical knowledge, curricular and experiential successively. Moreover, the images and attitudes of teachers regarding their teaching practice in higher education corroborate a traditional model of teaching, marked by emphasis of subject content to be taught at the expense of other types of knowledge, beyond the maternal image, vocational, feminist characterizing the teaching profession as a background. So the teacher´s look in the light of knowledge of social representations is an important discussion in teaching, since knowledge of representations can help to design training programs that meet the needs of management agencies, but considering the actual need of building a perceived and needed knowledge for teaching work.
Keywords: trabalho docente; representações sociais; saberes docentes; teaching work; social representations; knowledge teachers; CNPQ::CIENCIAS HUMANAS::EDUCACAO